Intercultural communication and diplomacy - Slavik, Hannah (DiploFoundation MsidaMT, 2004)
Looks at the theory and basics of intercultural communication and explores its practice in diplomacy. Deals with intercultural communication in negotiation and conflict resolution and focuses on communication between organisational and professional cultures.